1984
DOI: 10.2307/1942659
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Recruitment, Growth, and Mortality as Factors Maintaining Rain Forest Tree Diversity

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecological Monographs. Abstract. One general hypothesis to explain how for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
198
4
4

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(229 citation statements)
references
References 53 publications
16
198
4
4
Order By: Relevance
“…Quadrat-based analyses are likely to be more productive if long-term demographic data are available, and Connell et al (32) have found some frequency-dependent effects in two Queensland (Australia) rainforests.…”
Section: Discussionmentioning
confidence: 99%
“…Quadrat-based analyses are likely to be more productive if long-term demographic data are available, and Connell et al (32) have found some frequency-dependent effects in two Queensland (Australia) rainforests.…”
Section: Discussionmentioning
confidence: 99%
“…Most important, when trying to explain diversity in tropical forests, is the fact that the effect becomes stronger as species diversity increases. The assumptions of the hypothesis appear to be true in many systems, resulting in characteristic dispersion patterns (66,(81)(82)(83)(84), but it remains to be seen whether it can explain diversity or species composition. A limitation of the current paradigm-both theory and observation-is that it invokes no intrinsic species differences.…”
Section: Ch Ysophyllum Cainito Tachigali Versicolormentioning
confidence: 99%
“…Indeed, the existing empirical evidence for a CCTeffect appears weak (Connell et al 1984;Welden et al 1991;Webb & Peart 1999). Figure 3 illustrates why this may be the case in communities in which species share generalist pathogens.…”
Section: Introductionmentioning
confidence: 96%
“…Connell et al 1984). This relationship has been termed the community-level compensation trend (CCT; Webb & Peart 1999).…”
Section: Introductionmentioning
confidence: 99%